Spectrally stable and efficient pure-blue light-emitting diodes based on CsPb(Br/Cl)3 nanocrystals with surface passivation by organic sulfonate. (November 2022) - Sun, Siqi; Jia, Pei; Huang, Qizhang; Lu, Min; Lu, Po; Qin, Feisong; Sun, Guang; Gao, Yanbo; Bai, Xue; Wu, Zhennan; Zhang, Yu
Abstract: Despite rapid development of perovskite nanocrystal (PeNC) light-emitting diodes (LEDs), it remains challenging to achieve efficient and stable blue PeLEDs, especially for pure-blue PeLEDs required for displays. Mixed halide CsPb(Br/Cl)3 NC is a common strategy to achieve pure-blue emission, but suffers from low photoluminescence quantum yield (PLQY) and spectra instability. Here, a facile approach for the synthesis of high-quality pure-blue emitting CsPb(Br/Cl)3 NCs is reported by introducing an organic sulfonate, phenyl trifluoromethanesulfonate (PTFMS), which works as an efficient surface passivator. As a result, the optimized PeNCs achieve a high PLQY of 85% and enhanced conductivity. Furthermore, the LED based on the optimized PeNCs is developed with pure-blue emission at 469 nm, which yields an external quantum efficiency (EQE) of 1.20% and luminance of 355 cd m −2 . More impressively, the device shows excellent spectra and operation stability under voltage bias, resulting from the suppressed ion migration channels by efficient defect passivation. Graphical abstract: Image 1 Highlights: Phenyl trifluoromethanesulfonate passivated the defects on CsPb(Br/Cl)3 NC surface. The optimized PeNCs exhibited a high PLQY of 85% and improved conductivity. The pure-blue LED achieved a peak EQE of 1.20% and a high luminance of 355 cd m −2 . Efficient passivation suppressed ion migration and improved the EL stability.